Detailed morphological description of the mature larva of Globicornis corticalis (Eichhoff, 1863) (Dermestidae: Megatominae) with comparisons to related species - Kadej, Marcin; Jaroszewicz, Sylwia (Zootaxa, 2013)
A description of the last larval instar (based on exuviae) of Globicornis corticalis (Eichhoff, 1863) (Coleoptera: Dermestidae) is presented. Morphological characters of Globicornis larvae are characterized and discussed, including antenna, epipharynx, mandible, maxilla, ligula with labial palpi, hastisetae, legs, tergites, and condition of the antecostal suture. Structural differences among mature larvae of G. corticalis (Eichhoff, 1863), G. emarginata (Gyllenhal, 1808) and G. nigripes (Fabricius, 1792) are compared and summarized.